The gender and a chievement of nursing care - Geilsa Soraia Cavalcanti Valente; Elaine Antunes Cortez; Maira Muniz Assis; Rafaely Marins Machado; Audrey Vidal Pereira; Francisco Carlos Santos Junior (Universidade Federal do Estado do Rio de Janeiro, 2010)
Objective: To discuss how the relationships of gender among hospitalized patients and nursing staff at times of exposure of intimacy. Consists in thinking about the challenges of caregiving in nursing, based on client rights. Method: This is an exploratory study with quanti-qualitative approach, with the participation of twenty customers aged between 25 and 70 years, hospitalized in a private health institution, located in Niterói, based on Resolution No. 196 / 96 (CNS). Results and Conclusion: female customers (55%) have a higher preference for professionals of the same sex, as opposed to male clients (45%), which mostly demonstrated not have a preference as to sex work.